HuangqiGuizhiWuwu Decoction Prevents Vascular Dysfunction in Diabetes via Inhibition of Endothelial Arginase 1 - Cheng, Hong; Lu, Tian; Wang, Jingya; Xia, Yucen; Chai, Xiaoshu; Zhang, Minyi; Yao, Yutong; Zhou, Na; Zhou, Sisi; Chen, Xinyi; Su, Weiwei; Liu, Cunzhi; et al. (Frontiers in Physiology, 2020)
Hyperglycemia induces vascular endothelial dysfunction, which contributes to the development of vascular complication of diabetes. A classic prescription of traditional medicine, Huangqi Guizhi Wuwu Decoction (HGWWD) has been used for the treatment of various cardiovascular and cerebrovascular diseases, which all are related with vascular pathology. The present study investigated the effect of HGWWD treatment in streptozocin (STZ)-induced vascular dysfunction in mouse models. In vivo studies were performed using wild type mice as well as arginase 1 knockout specific in endothelial cells (EC-A1-/-) of control mice, diabetes mice and diabetes mice treated with HGWWD (60 g crude drugs/kg/d) for 2 weeks. For in vitro studies, aortic tissues were treated with mice serum containing HGWWD with or without adenoviral arginase 1(Ad-A1) transduction in high glucose (HG) medium. We found that HGWWD treatment restored STZ-induced impaired mean velocity and pulsatility index of mouse left femoral arteries, aortic pulse wave velocity and vascular endothelial relaxation accompanied by elevated NO production in the aorta and plasma, as well as reduced endothelial arginase activity and aortic arginase 1 expression. The protective effect of HGWWD is reversed by an inhibitor of nitric oxide synthesis. Meanwhile, the preventive effect of serum containing HGWWD in endothelial vascular dysfunction is completely blocked by Ad-A1 transductionin HG incubated aortas. HGWWD treatment further improved endothelial vascular dysfunction in STZ induced EC-A1-/-mice. This study demonstrates that HGWWD improved STZ-induced vascular dysfunction through arginase 1 – NO signaling, specifically targeting endothelial arginase 1.